Lichtwerke: Colour film by Henning Lohner, 1988 - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2008)
Scenes from MOMENTE ( 1965 ), HYMNEN ( 1968 ), HYMNEN with orchestra ( 1972 ),STIMMUNG in the caves of Jeita ( 1969 ), and especially MONDAY from LIGHT ( La Scala, Milan, 1988 ).Conversation with Stockhausen about Scenic Music and visions of the future.